Coastal monitoring strategy for geochemical detection of fugitive CO2 seeps from the seabed. (August 2015) - Greenwood, Jim; Craig, Peter; Hardman-Mountford, Nick
Highlights: We simulate a theoretical small-area CO2 seep at a potential sequestration site in Bass Strait, Australia. A simple procedure for the optimal positioning of monitoring instruments is described. The seep detection limit depends strongly on the number of instruments used. Delays of up to ∼2 months are possible between commencement of a seep and its subsequent detection. Abstract: A simple plume model is used to examine the near-field (100 km 2 ) dispersion characteristics of dissolved CO2 leaking from a small-area seabed seep in a vertically well-mixed coastal environment. We demonstrate how prior knowledge of the advective flow can be used to aid optimal positioning of monitoring stations capable of detecting seeps from anywhere in the area. As an example, a three-detector layout is proposed for a test site in Bass Strait, Australia, and an associated seep detection limit and monitoring time-scale for seep confirmation is identified. Dilution of the dissolved plume places strict limits on the minimum seep size that can be detected and depends non-linearly on the number of instruments used. Implications of the patchy nature of the dissolved plume, the potential future use of mobile detectors, and ability to account for background environmental variability, are highlighted.